Low-temperature electroless synthesis of mesoporous aluminum nanoparticles on graphene for high-performance lithium-ion batteries. Issue 23 (29th May 2019) - Zhang, Hongyu; Xia, Guanglin; Fang, Fang; Sun, Dalin; Yu, Xuebin
Abstract : A low-temperature electroless synthesis of mesoporous Al nanoparticles on graphene with advanced lithium storage performance. Abstract : The controllable fabrication of nanostructured Al at low temperature remains a great challenge for extending its application into emerging areas such as energy storage. Herein, we report a green and controllable electroless synthesis of mesoporous Al nanoparticles on graphene (mp-Al@G) using nontoxic Mg nanoparticles (NPs) and molten AlCl3 at a temperature as low as 190 °C. Moreover, the removal of the by-product (MgCl2 ) leads to the formation of mesopores inside the Al NPs, which are uniformly distributed on the graphene. The composite exhibits high reversible capacity and long cycle life when used as the anode material in lithium ion batteries. When coupled with a LiNi0.6 Co0.2 Mn0.2 O2 cathode, the full cell could also deliver an energy density of 455 W h kg −1 at a 1C rate, which demonstrates its potential application in high energy lithium ion batteries. These findings will trigger more investigations into developing Al as a high-performance energy storage material.